Response of upland rice to ploughing depth, nitrogen fertilization, and soil water status - Fernando Stone, Luis; Geraldo da Silva, José (Pesquisa Agropecuaria Brasileira, 1998)
The effects of N levels (0, 40, and 80 kg of N/ha), N split application (no split, 1/3 at sowing and 2/3 at panicle initiation, and 1/3 at sowing and 2/3 at flowering), ploughing depth (10-15 cm and 30-35 cm), and water stress (with and without) on yield of upland rice (Oryza sativa L.) cultivars Rio Paranaíba and Maravilha were studied during two years, with the objective of determining the most suitable soil and nitrogen fertilization management under water stress conditions. Under these conditions, yield decrease was more severe for Maravilha, for being a favourable upland rice cultivar. In the absence of a soil compacted layer, ploughing should be done at 10-15 cm deep. The most adequate nitrogen level was 40 kg/ha. In regions with water deficit it is necessary to split N fertilization, as following: 1/3 at sowing and 2/3 at flowering initiation. N cover only should be done if rice crop shows adequate development and when there is enough soil water to supply rice plants for, at least, ten days after flowering initiation.